Bisphenol A analogues bisphenol B, bisphenol F, and bisphenol S induce oxidative stress, disrupt daily sperm production, and damage DNA in rat spermatozoa: a comparative in vitro and in vivo study. (April 2019) - Ullah, Asad; Pirzada, Madeeha; Jahan, Sarwat; Ullah, Hizb; Khan, Muhammad Jamil
Bisphenol A (BPA) is a well-known endocrine-disrupting chemical with estrogenic activity. The widespread exposure of individuals to BPA is suspected to affect a variety of physiological functions, including reproduction, development, and metabolism. Here we report the mechanisms by which BPA and three of its analogues bisphenol B (BPB), bisphenol F (BPF), and bisphenol S (BPS) cause generation of reactive oxygen species (ROS), sperm DNA damage, and oxidative stress in both in vivo and in vitro rat models. Sperm were incubated with different concentrations (1, 10, and 100 µg/L) of BPA and its analogues BPB, BPF, and BPS for 2 h. BPA and its analogues were observed to increase DNA fragmentation, formation of ROS, and affected levels of superoxide dismutase at higher concentration groups. In an in vivo experiment, rats were exposed to different concentrations (5, 25, and 50 mg/kg/day) of BPA, BPB, BPF, and BPS for 28 days. In the higher dose (50 mg/kg/day) treated groups of BPA and its analogues BPB, BPF, and BPS, DNA damage was observed while the motility of sperm was not affected.